Management, bullying and the work outcomes of Australian paramilitary. Issue 3 (September 2017) - Brunetto, Yvonne; Xerri, Matthew; Shacklock, Kate; Farr-Wharton, Ben; Farr-Wharton, Rod
This study compared the impact of perceived organisational support from management upon bullying of soldiers and police officers and their work outcomes (wellbeing, affective commitment and turnover intentions). Data from self-report surveys from 99 army personnel and 193 police officers were analysed using SEM. The results indicate that significant paths between most variables and perceived organisational support explained 6% of bullying (comprising intimidation and personal attacks). Together, (a) perceived organisational support and bullying explained almost a third (28%) of psychological wellbeing, (b) perceived organisational support, bullying and psychological wellbeing explained over two-thirds (68%) of affective commitment, and (c) bullying and affective commitment explained over half (53%) of turnover intentions. Also, bullying partially mediated the relationship between perceived organisational support and affective commitment. There were no significant differences between the two cohorts, except for perceived organisational support from management. Implications include that soldiers and police officers are likely to experience better workplace performance if management support is improved. Both soldiers and police undertake emotionally difficult tasks at times, and without adequate support, the stress of their jobs is likely to negatively impact their wellbeing and commitment. Poor perceived management support is not sustainable in the long-term without negative employee consequences.